2021
DOI: 10.1101/2021.04.02.438257
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

The m6A landscape of polyadenylated nuclear (PAN) RNA and its related methylome in the context of KSHV replication

Abstract: Polyadenylated nuclear (PAN) RNA is a non-coding transcript involved in Kaposis sarcoma-associated herpesvirus (KSHV) lytic reactivation and regulation of cellular and viral gene expression. We have shown that PAN RNA has a dynamic secondary structure and protein binding profiles that can be influenced by the epitranscriptomic modifications. N6-methyladenosine (m6A) is an abundant signature found in viral and virus-encoded RNAs. Here, we combined an antibody-independent next generation mapping with direct RNA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…The m 6 A-eCLIP confirmed previous results seen where upon reactivation there is an overall decrease in methylation on host transcripts and a massive increase in methylation of viral transcripts [35,36,42]. Furthermore, we observed a 5' UTR hypomethylation and a concomitant 3' UTR hypermethylation following KSHV reactivation from latency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The m 6 A-eCLIP confirmed previous results seen where upon reactivation there is an overall decrease in methylation on host transcripts and a massive increase in methylation of viral transcripts [35,36,42]. Furthermore, we observed a 5' UTR hypomethylation and a concomitant 3' UTR hypermethylation following KSHV reactivation from latency.…”
Section: Discussionsupporting
confidence: 90%
“…Recent transcriptome-wide m 6 A mapping of multiple viruses [35][36][37][38][39][40] have brought to the forefront research concerning a complex interplay between the m 6 A pathways and viral replication success. Previous research has shown that KSHV can hijack this system to deposit m 6 A onto its own transcripts, including KSHV ORF50 (RTA), the master latent-to-lytic switch protein and on the multifunction long-noncoding RNA (lncRNA) PAN [36,[41][42][43]. While there is strong evidence that the m 6 A landscape is reshaped during KSHV infection, and that this shifts ultimately promotes the progression of KSHV infection, it remains unclear whether this m 6 A repurposing also affects the fate of host transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of discoveries on ncRNAs have been recently demonstrated in various fields such as oncology, cardiology, virology, and others (1)(2)(3)(4)(5)(6). ncRNAs are divided into different classes based on their size, architecture and mechanisms of action.…”
Section: Ncrnas Shaping the Future Of Humankindmentioning
confidence: 99%